The conceptualisation of Eye and Mouth Idioms in Bura - Salihu, Maria Mbursa (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
This paper focuses on a comparison between Bura and English body part idioms. The objectives are to compare the meanings conveyed by Bura and English eye and mouth idioms and to examine which conceptual process motivates the Bura and English eye and mouth idioms. In total, 30 eyes and mouths related idioms were identified and included in the study. The idioms were extracted from Bura print material such as Holy Scripture and daily conversations of Bura people and English idiom from Longman Idiom Dictionary online (2022). The eye and mouth idiom were evaluated for meaning and cross-domain similarity based on the Conceptual Metaphor Theory (CMT). Analysis of the data showed that idioms are neither entirely same nor different for each language. Also, more similarities have been discovered, but the conceptualisation of the meaning of a specific mouth and eye idiom (Bura and English) involves a combination of two or more conceptual motivations. The results provide more evidence of the universality of idioms in all languages.